The chocolate war - Cormier, Robert (New York : Knopf : Distributed by Random House, 2004)
A high school freshman discovers the devastating consequences of refusing to join in the school's annual fund raising drive and arousing the wrath of the school bullies.
Originally published: New York : Pantheon Books, c1974.
Keywords: High schools -- Fiction; Schools -- Fiction